Design of A Web-Based Goods Recording Application at PT. Cahaya Cutter Prima - Yudi Baskara (Komunitas Dosen Indonesia, 2022)
Today, the progress and development of Information Technology has penetrated into various aspects of human life. The recording of incoming goods and outgoing goods is an activity carried out by a company to control and track the amount of goods available in the company. The system used by PT. Cahaya Cutter Prima still uses a manual process. The concept of a manual goods recording system causes incorrect information from the warehouse. As a end result of the misinformation, ensuing in a discrepancy among the facts entered with the present goods. This system to help personnel in calculating the quantity of products to be effective and efficient to decide the quantity of inventory. As a basis for reference to create an information system for recording incoming and outgoing goods, a literature study was conducted using the Waterfall method as a reference in the design of this information system, starting with the design of a database using ERD. The programming language used is PHP with Bootstrap framework and MySQL as the database. It can be concluded that the results of the implementation of this new system can help companies more easily, efficiently, and effectively. It is expected that the efficiency of the company will increase and the work done will become easier. The information needed by the company is also qualified so that the decisions taken can have a positive impact on the company.